Building urban climate resilience: learning from the ACCCRN experience in India - Sharma, Divya; Singh, Raina; Singh, Rozita (International Journal of Urban Sustainable Development, 2014)
This article highlights the various methodologies adopted for the preparation of climate resilience strategy in seven cities (Surat, Indore, Gorakhpur, Guwahati, Shimla, Bhubaneswar and Mysore) of India under the Asian Cities Climate Change Resilience Network (ACCCRN) programme. It analyses these methodologies and the overall processes adopted in each of these cities for its potential for replication and brings out the inherent challenges, gaps and opportunities in achieving this.Discussions with the key city stakeholders involved in the ACCCRN process and implementing partners were conducted to understand their views on the need and efficacy of resilience planning in Indian cities as well as the challenges encountered by them during the process. Several issues and suggestions that have emerged from the experiences of the city stakeholders could guide city-level engagements in future. Based on these experiences, key lessons have been highlighted with the aim of guiding the cities to undertake urban resilience planning in future.
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:urban climate resilience; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13588 Concepts and Determinants of Regional Economic Resilience; openalex:import; openalex:yes